Former Road Cyclists Still Involved in Cycling Report Lower Burnout Levels Than Those Who Abandoned This Sport - Sors, Fabrizio; Tomé Lourido, David; Damonte, Stella; Santoro, Ilaria; Galmonte, Alessandra; Agostini, Tiziano; Murgia, Mauro (Frontiers in Psychology, 2020)
Despite the numerous benefits associated with sport practice, many children and adolescents end up quitting it year after year, with a stable dropout rate between 10 and 19 years of age. Among the causes of sport abandonment, the scientific literature highlights the presence of burnout as a fundamental factor. In this regard, the aim of the present study was to investigate the levels of the three components of sport burnout–emotional and physical exhaustion, reduced sense of accomplishment, and sport devaluation–reported by a sample of young (former) athletes, depending on whether their sport abandonment was relative (i.e., change to another sport modality) or definitive. In particular, participants were former agonist road cyclists, who have been divided into three groups on the basis of what they did after abandoning road bicycle racing, namely: (a) those still involved in cycling, either in a different specialty (e.g., mountain bike) or with a different role (e.g., coach for kids); (b) those who started practicing a different sport; and (c) those who definitively abandoned sports. The general hypothesis was that, with respect to those who changed sport and those who definitively abandoned it, those still involved in cycling would report experiencing lower levels of the three burnout components during the last year practicing it. To test this hypothesis, the Athlete Burnout Questionnaire (ABQ; Raedeke and Smith, 2001) was administered to 85 young former road cyclists. The results seem to support the hypothesis for two out of the three components, namely, emotional and physical exhaustion and sport devaluation; on the other hand, for reduced sense of accomplishment, no difference among the three groups emerged. Further research is needed to deepen the understanding of such processes, also in relation with other relevant constructs; yet, the results of the present study should already raise the awareness of sport organizations on the need to deal with this and related phenomena by adopting appropriate strategies to ensure the well-being of young athletes, thus trying to reduce early dropout.